2016
DOI: 10.1177/1088767916666603
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Analysis of Homicide Across Brazil’s Municipalities

Abstract: Examining homicide across Brazil’s 5,562 municipalities, we find that violence nearby has a positive effect on local violence (diffusion effect), violence exerts an unusual negative spatial effect in small clusters of communities in northeastern Brazil, and a prominent poverty-reduction program (Bolsa Família [BF]) has mixed effects. The spatial dimensions of violence complement existing non-spatial research on violence in Brazil, and the results regarding BF offer a spatial complement to research on condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…For dissemination, Ingram and da Costa found evidence across most Brazilian regions for spatial dissemination, i.e. positive association in homicide rates among neighboring municipalities, but only using cross-sectional data from a single year (Ingram 2017 ). By contrast, Peres and Nivette used longitudinal methods and found that steep increases in a small number of municipalities explained a large proportion of the nationwide homicide increase from 1991 to 2010 (Peres and Nivette 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For dissemination, Ingram and da Costa found evidence across most Brazilian regions for spatial dissemination, i.e. positive association in homicide rates among neighboring municipalities, but only using cross-sectional data from a single year (Ingram 2017 ). By contrast, Peres and Nivette used longitudinal methods and found that steep increases in a small number of municipalities explained a large proportion of the nationwide homicide increase from 1991 to 2010 (Peres and Nivette 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, shootings are frequent in places where other illicit activities, such as drug dealing, take place (Blumstein, 1995;Lum, 2008); open drug markets often entail violence as a consequence of the simultaneous presence of firearms, young dealers, suitable targets (both profitable street joints and large cash amounts), and intensive law enforcement (Chaiken & Chaiken, 1990;Reuter, 2009;Tonry, 1990). Furthermore, spatial proximity to episodes of violence and prior homicides help explain the concentration of interpersonal violence in specific locations (Ingram & Costa, 2016;Morenoff, Sampson, & Raudenbush, 2001). Community risk factors include the sociodemographic characteristics of the places where crime occurs.…”
Section: Organized Crime-and Gang-related Violencementioning
confidence: 99%
“…This pattern is in line with what is observed in other studies, although, most of those studies are focused on a specific group or category of mortality from external causes (5, 19, 31–36). In the states of the South and Southeast regions, mortality from homicides increased between 1980 and 2000, while in Northern and Northeastern states, violent deaths rose more markedly after 2000 ( 31 – 34 ). At the state level, between 2001 and 2011 in all Northeastern states (except Pernambuco), homicide rates increased ( 31 ).…”
Section: Discussionmentioning
confidence: 99%